Juridical Review of the Legal Status of Children Born Through Womb Renting in Indonesia - Marnipera Ngerika Sihombing; Martono Anggusti; Roida Nababan (Journal of Legal and Cultural Analytics, 2025)
Womb rental is a method of obtaining offspring by using another woman's womb to contain an embryo derived from the egg and sperm of a married couple. After the child is born, it will be handed back to the married couple who owns the embryo. The implementation of uterine leasing is prohibited in Indonesia because it is contrary to applicabl’e laws and regu’lations and contrary to religious norms. This st’udy aims to determine the legal status of children born through uterine leasing based on positive law in In’donesia. This researc’h uses norm’ative legal resea’rch. Based on the res’ults of the stu’dy, if the st’atus of the surro’gate mother is a g’irl or widow, th’en the child is an unmarried ch’ild, where children born out’side of marria’ge only have a ci’vil relation’ship with their moth’er and th’eir mother's fam’ily. If the s’tatus of the surr’ogate mother is bou’nd by a legal marriag’e (has a husb’and), then the ch’ild born is the legiti’mate child of the su’rrogate mother and her hu’sband.